Federal Police officers and political transformations in the province of Córdoba (1943-1949) (Quinto Sol, 2025)
In this article, we address the impact of political and state centralization measures promoted by Peronism by studying the reorganization of the structure of the Córdoba police force, headed by Federal Police officers. In this regard, we identify the Inter-American Conferences on the Coordination of Police and Judicial Measures, held during World War II, as spaces that enabled the emergence of federal-level police cooperation organizations that relied on national defense, along with the maintenance of neutrality, to legitimize police action in matters of internal security. At the same time, from a national perspective, we investigate the context of political and partisan disputes following the 1943 coup d'état and their implications for the Córdoba police force. As demonstrated, the modifications included internal provisions (personnel regimes and technical infrastructure) and the passage of a police law that enshrined their unification under a single authority: the provincial police chief. This research aims to provide a series of perspectives for studying the role of police institutions in the affirmation and consolidation of government political power.
Keywords: Police; internal security; legislation; centralization